1980
DOI: 10.1007/bf00279044
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial deletion of the long arm of chromosome 7

Abstract: Chromosome studies were carried out in a girl because of psychomotor retardation and difficulty in swallowing. The girl was admitted to hospital for the first time when 25 months old. The most characteristic signs revealed by the physical examination were short distal ulnar phalanges, clitoral hypertrophy, and very thin outer ear cartilages. An interstitial deletion of the long arm of chromosome 7 was observed: 7q22::7q31. Laboratory investigations revealed a remarkably high levels of IgG, immunoglobulin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…It is only recently that nontelomeric uncharacterized microdeletions have the potential to be discovered, using the array-CGH technology. Cytogenetically detectable interstitial deletions of 7q have been reported previously [Serup, 1980;Young et al, 1984;Sarda et al, 1988]. For example, Sarda et al [1988] reported an interstitial deletion involving 7q31.2-q32.3 in a 7-year-old boy who presented with dysmorphic features of the face and absence of speech, despite language comprehension and psychomotor development equivalent to those of a 5-yearold.…”
Section: Discussionmentioning
confidence: 88%
“…It is only recently that nontelomeric uncharacterized microdeletions have the potential to be discovered, using the array-CGH technology. Cytogenetically detectable interstitial deletions of 7q have been reported previously [Serup, 1980;Young et al, 1984;Sarda et al, 1988]. For example, Sarda et al [1988] reported an interstitial deletion involving 7q31.2-q32.3 in a 7-year-old boy who presented with dysmorphic features of the face and absence of speech, despite language comprehension and psychomotor development equivalent to those of a 5-yearold.…”
Section: Discussionmentioning
confidence: 88%
“…However, subsequent studies using R-and G-banding [de Grouchy et al, 19741 showed that the defect involved a nonreciprocal translocation from chromosome 6 to 7, effectively making the patient monosomic for the region distal to 7q32. Since that first report, another 32 cases of del (7q) have been described, including 15 terminal deletions [Bass et al, 1973;Bernstein et al, 1980;Biederman and Bowen, 1978;Francke, 1978;Friedrich et al, 1979;Harris et al, 1977;Kodama et al, 1980;Kousseff et al, 1977;Shokeir et al, 1973;Taysi et al, 1982;Turleau et al, 19791 and 17 interstitial deletions [Ayraud et al, 1976;Crawfurd et al, 1979;Dennis et al, 1977;Franceschini et al, 1978;Gibson et al, 1982;Higginson et al, 1976;Johnson et al, 1978;Klep-de-Pater et al, 1979;Nielsen et al, 1979;Seabright and Lewis, 1978;Serup, 1980;Stallard and Juberg, 1981;Valentine and Sergovich, 19771. Three patients with a ring 7 chromosome [Nakano and Miyamoto, 1977;Zackai and Breg, 19731 and one with a 7q terminal deletion associated with trisomy 9p [Turleau et al, 19741 have also been reported but are not included in our review of the dysmorphogenetic effects of del (7q) (Table I) because they are aneusomic for segments of the genome other than 7q and therefore do not represent pure 7q monosomy.…”
Section: Introductionmentioning
confidence: 97%
“…The observation of three cases of ectrodactyly in proximal deletions 7q:7q11.2q22 [Pfeiffer, 1984; present case] and 7qllq21 or 22 [Del Porto et al, 19831 suggests a causal relationship, but more information is needed to confirm this. References Valentine and Sergovich, 1977Ayraud et al, 1976Higginson et al, 1976Dennis et al, 1977Franceschini et al, 1978Klep-de Pater et al, 1979Serup, 1980Abuelo and Padre-Mendoza, Young et al, 1984Martin-Pont et al, 1985Johnson et al, 1978Seabright and Lewis, 1978Klep-de Pater et al, 1979Crawfurd et al, 1979Gibson et al, 1982Del Porto et al, 1983Pfeiffer, 1984Young et al, 1984Fryns et al, 1985Frydman et al, 1986 …”
Section: Discussionmentioning
confidence: 98%